PENERAPAN PROBLEM-BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL DUA DIMENSI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA - Festya Saraswati Citra Afriani; Ratno Abidin; Titik Kurniawati (Universitas Muhammadiyah Surabaya, 2024)
One way to solve the problem of students' low speaking skills in elementary schools is by implementing the Problem-Based Learning (PBL) learning model. The purpose of writing this article or research is to determine the application of the Problem-Based Learning (PBL) learning model using two-dimensional audio-visual media in order to improve students' speaking skills in Indonesian language subjects, retelling the contents of fictional stories and explaining their intrinsic elements in words. -words themselves logically, systematically, effectively and creatively. This research was carried out in class V-B of SDN Penjaringansari II/608 Surabaya. The research subjects were class V-B which consisted of 30 students. The data in this study consisted of speaking skills tests and written tests in the form of LKPD (Students' Worksheets). The results of the speaking skills test were taken from group observations during the presentation. The research results showed that when giving assignments via Student Worksheets (LKPD), the majority of students (80%) were able to understand fictional stories well and retell them briefly in written form, and could explain their intrinsic elements correctly. Speaking skills are measured through group presentations. The research results showed that all groups were able to fulfill the criteria very well for retelling according to the content of the story and using grammar, vocabulary and expressions correctly and variedly. In terms of language fluency criteria, 50% of students still need to improve their ability to pronounce language during presentations so that listeners can understand them well. On the criteria of expression and self-confidence, there are 67% of students who still need to improve their expression and self-confidence when making presentations. This shows that some parts of students still feel shy, nervous and lack of self-confidence.